Dual deconvolution algorithm: analysis code with experimental data - Wonshik Choi (18877660) (2025)
This software package provides key algorithms for dual-deconvolution microscopy analysis, along with both experimental and numerical data. The dual-deconvolution algorithm is an advanced deep-tissue imaging technique designed to measure fluorescence signals from thick, aberrated samples. It incorporates virtual structured illumination microscopy (SIM) and computational adaptive optics to achieve super-resolution imaging. The package includes comprehensive algorithm implementations and data to facilitate the broader adoption of dual-deconvolution in deep-tissue imaging applications. The reference URL available on the archive: https://doi.org/10.48550/arXiv.2404.11849 The code has been validated for use in MATLAB R2020a, R2021a, R2022a, R2023a, R2024a, R2024b, and R2025a environments. Two essential toolboxes must be installed during the MATLAB installation process: the Signal Processing Toolbox and the Image Processing Toolbox. All code and datasets have been developed and tested by Seok-chan Yoon (Pusan University) and Su-min Lim (Korea University), members of the Super-Depth Imaging Group (https://www.bioimaging.korea.ac.kr/).